Between Career and Family: The Role of Self-Efficacy in the Subjective Well-Being of Women with Dual Roles - Oktaviani, Isdiyanti Dwi (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Women who work while also fulfilling the role of a mother are expected to be responsible for supporting their children's development. The increasing number of women who perform multiple roles has become an important phenomenon that needs attention, as it may influence individual subjective well-being. This study aimed to examine the effect of self-efficacy on subjective well-being among women with multiple roles based on empirical data. A total of 110 participants were selected using a non-probability purposive sampling method, with the criteria of women who work outside the home, are aged 20–40 years, have children aged 1–12 years, and live with their husbands and children in daily life. Subjective well-being was measured using the scale developed by Adywardoyo (2017), while self-efficacy was measured using a scale adapted from Schwarzer et al. (2002). The results of simple linear regression analysis showed that self-efficacy had a significant effect on subjective well-being. For the life satisfaction aspect, the analysis produced F = 13.459, p < 0.05, and R² = 0.111, while for the affective aspect, F = 9.239, p < 0.05, and R² = 0.068. These findings indicate that self-efficacy contributes to the improvement of subjective well-being, suggesting that strengthening self-efficacy is an important factor in enhancing subjective well-being among women with multiple roles.Wanita yang bekerja dan juga berperan sebagai ibu diharapkan dapat bertanggung jawab dalam mendampingi perkembangan anak-anak mereka. Peningkatan jumlah wanita yang mengemban peran ganda menjadi fenomena penting yang perlu diperhatikan. Penelitian ini bertujuan untuk melakukan pengujian berdasarkan data nyata pengaruh self-efficacy terhadap subjective well-being pada wanita dengan peran ganda. Sebanyak 110 partisipan dipilih menggunakan metode non-probability purposive sampling, dengan kriteria wanita yang bekerja di luar rumah, berusia 20 hingga 40 tahun, memiliki anak berusia 1-12 tahun, dan tinggal bersama suami serta anak-anak dalam kehidupan sehari-hari. Skala subjective well-being dari Adywardoyo (2017) digunakan untuk mengukur subjective well-being, sementara skala self-efficacy yang diadaptasi dari Schwarzer et al. (2002) digunakan untuk mengukur self-efficacy. Hasil pengujian hipotesis dengan analisis regresi linier sederhana menunjukkan nilai F sebesar 13.459 untuk aspek kepuasan hidup dan 9.239 untuk aspek afektif, dengan nilai signifikansi 0,000 (p < 0,05) untuk aspek kepuasan hidup dan 0,003 (p < 0,05) untuk aspek afektif. Nilai R Square menunjukkan 0,111 untuk aspek kepuasan hidup dan 0,068 untuk aspek afektif. Hasil ini menunjukkan bahwa self-efficacy berkontribusi terhadap peningkatan kesejahteraan subjektif, sehingga penguatan self-efficacy menjadi salah satu faktor penting dalam upaya meningkatkan subjective well-being pada wanita dengan peran ganda.